PENGARUH ENTREPRENEURIAL PASSION, ENTREPRENEURIAL EDUCATION, DAN ENTREPRENEURIAL MINDSET TERHADAP ENTREPRENEURIAL INTENTION PADA MAHASISWA IBM UNIVERSITAS CIPUTRA SURABAYA - Christina Whidya Utami; Faradillah, Bella (Universitas Ciputra Surabaya, 2023)
The purpose of this study is to to find out the influence of entrepreneurial passion, entrepreneurial education, and entrepreneurial mindset on entrepreneurial intention in IBM-RC students class of 2019 at Ciputra University Surabaya. This research type is quantitative research. The population in this research were IBM-RC students class of 2019. The sample in this research amounts to 198 respondents with online questionnaire data collection method, that is Google form. Sampling technique of this research uses non-probability sampling, that is purposive sampling. In this research, data is processed by using multiple linear regression analysis with SPSS software. The results of this research indicate that entrepreneurial passion influences significant on entrepreneurial intention, entrepreneurial education influences significant on entrepreneurial intention, entrepreneurial mindset influences significant on entrepreneurial intention.